Probabilistic theory of structures - Elishakoff, Isaac (Dover Publications, 1999)
Annotation Well-written introduction covers the elements of the theory of probability from two or more random variables, the reliability of such multivariable structures, the theory of random function, Monte Carlo methods of treating problems incapable of exact solution, and more. No previous knowledge of the subject necessary. Numerous examples, illustrative figures.
Slightly rev. ed. and updated ed. of: Probabilistic methods in the theory of structures. New York : Wiley, c1983.
Keywords: Structural analysis (Engineering); Probabilities.; elektronické knihy; electronic books